You got a rock, Charlie Brown! - Schulz, Charles M. (Charles Monroe), 1922-2000; Testa, Maggie (Ready-to-read. Superstar reader!, 2015)
The Peanuts gang celebrates Halloween, and Charlie Brown seems to have the worst luck.